Analysis of the change in disease burden of myocarditis in China from 1990 to 2019 - Wei SHI; Xuan-Xuan CUI; Wu-Ming ZHOU; Tian-Feng HUA; Min YANG (Yixue xinzhi zazhi)
Objective To describe the disease burden level and changing trend of myocarditis in China from 1990 to 2019.Methods According to the global burden of disease (GBD) 2019 database, the incidence, mortality, disability-adjusted life year (DALY), years lost due to disability (YLD), years of life lost due to premature death (YLL) and their age-standardized rate (ASR) and average annual percent change (AAPC) of myocarditis in China and the world from 1990 to 2019 were compared and analyzed, and the disease burden of myocarditis in different age and gender groups in China was expounded.Results Myocarditis incidence cases and deaths increased in China by 47.47% and 50.22%, respectively, compared to 1990, whereas DALY and YLL reduced by 25.59% and 28.02%, and YLD rose by 89.50%. Myocarditis incidence cases and mortality increased by 62.19% and 65.40% globally in 2019, DALY and YLL reduced by 0.42% and 2.53%, respectively, and YLD rose by 64.21%. Myocarditis incidence cases, mortality, and DALY cases all displayed a bimodal distribution in China in 2019 and peaked at ages under 20. In China, the AAPC for standardized incidence, mortality, and DALY rates were -0.223% (-0.233%, -0.213%), -0.612% (-0.812%, -0.411%), and -1.759% (-1.909%, -1.609%), respectively, from 1990 to 2019. The standardized incidence, standardized mortality and standardized DALY rate of global myocarditis AAPC were -0.157% (-0.164%, -0.151%), -0.257% (-0.395%, -0.117%) and -1.21% (-1.312%, -1.109%), respectively. In China, men experience more myocarditis incidence, death, and DALYs than women.Conclusion Compared with 1990, in 2019, the standardized incidence, standardized mortality and standardized DALY rate of myocarditis in China showed a downward trend, but there is still a greater threat to young people and the elderly, especially young men and elderly women. We should constantly strengthen the diagnosis and prevention of myocarditis.